One Health investigation of the antimicrobial resistome, genetic diversity and public health risk of toxigenic Clostridioides difficile isolated from humans and animals in Gauteng, South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2025)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2024.